Anisotropi Magnetik Film Tipis TiO2:Co yang Ditumbuhkan dengan Teknik MOCVD - Horasdia Saragih; Pepen Arifin; Mohamad Barmawi (Institut Teknologi Bandung, 2005)
TiO2:Co thin films have been successfully deposited by using MOCVD technique. The titanium (IV) isopropoxide [Ti(OCH(CH3)2)4] 99,99%, tris (2,2,6,6-tetramethyl-3, 5-heptanedionato) cobalt (III) 99%, and oxygen gas (O2) were used as Ti, Co, and O precursors, respectively. Crystal structure, morphology and magnetic properties of thin films were investigated by X-ray diffractometer (XRD), scanning electron microscope (SEM), and vibrating sample magnetometer (VSM), respectively. The magnetic anisotropy (K) of thin films was very strong depended on the growth temperatures. The thin film grown at temperature of 400°C has anatase-213 structure and K value of 40000 Oe.emu/cm3. At the growth temperature of 450°C, the thin films were has still anatase-213 and K value of 95000 Oe.emu/cm3. At growth temperature of 500°C, the thin films have K value of 72000 Oe.emu/cm3. The crystal structure of films was changed with an additional plane of anatase-301. The thin film grown at temperature of 550°C has K value of 103600 Oe.emu/cm3. The structure of thin film was polycrystalline, mixed by anatase-213, rutile-220 and TiCoO3 (310) phase. All of films have thickness of about 0,7-0,9 µm.